Saving Mali's desert elephants from war and poaching: a successful model of national and community engagement - Martin, Vance, speaker; van Hoven, Wouter, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Do poor villagers need elephants? The local people of Central Mali (West Africa) -- many ethnicities and clans -- know that elephants attract the attention (and therefore the assistance) of the wider community -- national, and international -- and are proud of that. As they say, "If the elephants disappear, our area will no longer be special." They also view elephants as an indicator of a healthy ecosystem and they know that their livelihoods depend on a healthy ecosystem. They also know from direct experience that elephants are important as seed dispersers and in forest regeneration. Elephants knock down otherwise inaccessible fruits and seeds from high branches that are gathered by the women for food and sometimes sale. Fruits and leaves are also eaten by livestock. Dung is valued to help conjunctivitis, a widespread problem in these environments. Over 12 years, The WILD Foundation and its many partners developed the Mali Elephant Project (MEP) as a very successful model of CBNRM. With engagement from local communities to the head of state, MEP has brought attention, action, and protection to this unique herd of elephants (the northern most in Africa, desert-adapted, and with the longest recorded elephant migration). It is now "war-tested" with only 2 elephants poached during the Tuareg rebellion and jihadist invasion of 2013. Yet local bandits remain, and the single biggest poaching incident in Mali's history occurred on the full moon night of the 13th/14th May 2014. But the local communities and the army solved it!
Moderator: Wouter van Hoven.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses